(untitled) (Argos, 2024)
The Imagines of Philostratus contain a significant number of violent scenes, especially those dedicated to the hero Heracles (2.21, 23, 25). Most of the critics have interpreted this motif as an exaltation of the heroic ideals of the Greek past in the paideia of the imperial elite; other readings propose to interpret the ekphráseis as expressions of a broader aesthetic of horror, which affects the sculptural iconography of the 2nd and 3rd centuries AD. The new aesthetic paradigms are related to the spectacle of furor as entertainment and publicity of the imperial ideology of power. This paper attempts to reconsider these theses in the light of the relationship between ferocity, strength, athletics and spectacle according to the visual aesthetics and sequentiality of the ekphráseis in the gallery and in continuity with the work Gymnasticus, where these topics are programmatic.